Acquired resistance to gemcitabine and cross-resistance in human pancreatic cancer clones. Issue 1 (January 2015) - Yoneyama, Hiroshi; Takizawa-Hashimoto, Asako; Takeuchi, Osamu; Watanabe, Yukiko; Atsuda, Koichiro; Asanuma, Fumiki; Yamada, Yoshinori; Suzuki, Yukio
<x xml:space="preserve">Abstract</x> The efficacy of gemcitabine (GEM), a standard treatment agent for pancreatic cancer, is insufficient because of primary or acquired resistance to this drug. Patients with tumors intrinsically sensitive to GEM gradually acquire resistance and require a shift to second agents, which are associated with the risk of cross-resistance. However, whether cross-resistance is actually present has long been disputed. Using six GEM-resistant and four highly GEM-resistant clones derived from the pancreatic cancer cell line BxPC-3, we determined the resistance of each clone and parent cell line to GEM and four anticancer agents (5-FU, CDDP, CPT-11, and DTX). The GEM-resistant clones had different resistances to GEM and other agents, and did not develop a specific pattern of cross-resistance. This result shows that tumor cells are heterogeneous. However, all highly GEM-resistant clones presented overexpression of ribonucleotide reductase subunit M1 (RRM1), a target enzyme for metabolized GEM, and showed cross-resistance with 5-FU. The expression level of RRM1 was high; therefore, resistance to GEM was high. We showed that a tumor cell acquired resistance to GEM, and cross-resistance developed in one clone. These results suggest that only cells with certain mechanisms for high-level resistance to GEM survive against selective pressure applied by highly concentrated GEM. RRM1 may be one of the few factors that can induce high resistance to GEM and a suitable therapeutic target for GEM-resistant pancreatic cancer.